Study of correlation of hypothyroidism with diabetic microvascular complications in type 2 diabetic adult Indian females - Chauhan, Devendra S.; Kushwaha, J. S.; Giri, Richa; Gautam , S. K. (International Journal of Advances in Medicine, 2023)
Background: Patients with type 2 diabetes mellitus are more prone to thyroid disorders. Hypothyroidism in them leads to an aggravation of microvascular complications. Screening for thyroid dysfunction in diabetic patients will allow early treatment of hypothyroidism. The aim of this study is to assess the correlation of hypothyroidism with diabetic microvascular complications. Methods: This is a cross‑sectional study that was conducted at department of medicine GSVM Medical College, Kanpur. 200 female patients with type 2 diabetes mellitus attending the out‑patient department were included. Subjects with any prior history of thyroid disease, chronic liver disease, or acute illness were excluded from the study. Results: Our study describes 14% prevalence of hypothyroidism (subclinical hypothyroidism 13.5%) among 200 diabetic subjects. Among hypothyroid patients 64.29% patients had nephropathy, 60.71% patients had neuropathy, 64.29% patients had retinopathy whereas euthyroid patients had 26.74%, 25% and 29.07% nephropathy, neuropathy, and retinopathy respectively. Conclusions: The prevalence of hypothyroidism was 14% among female patients with type 2 diabetes mellitus in this study. Overt hypothyroidism was 0.5 % and subclinical hypothyroidism was more common (13.5%) among the study subjects. Patients having hypothyroidism were more likely to be having diabetic nephropathy, neuropathy, and retinopathy.